Pengembangan Instrumen Tes HOTS dalam Mengukur Kemampuan Berpikir Kritis Siswa SMP Kelas VIII Materi Lingkaran - Nurul Syamsiah; Marhadi Saputro; Yadi Ardiawan (Journal of Creative Student Research, 2023)
This study aims to develop a higher order thinking skill (HOTS) test instrument which is used to measure students' critical thinking skills on circular material. This research was conducted at SMP Negeri 7 Putussibau using the research and development method of the Borg and Gall research design with 10 stages, namely, potential and problems, data collection, product design, design validation, design revision, product testing, product revision. , trial use, product revision and mass product. But in this study only up to stage 8, namely the use trial. Based on the results of the research that has been carried out, it was found that the results of the validation of the HOTS test instrument from the three experts were in the valid category. While the effectiveness of the HOTS test instrument based on the results of the analysis is included in the effective category. The final form of the product of this research is the HOTS test instrument as many as 3 essay questions which are used to measure students' critical thinking skills.